Molecular Characterization of the T Cell Repertoire Using Immuno-scope Analysis and its Possible Implementation in Clinical Practice - Ria, F.; Elzen, P.; Madakamutil, L.T.; Miller, J.E.; Maverakis, E.; Sercarz, E.E. (Current Molecular Medicine, 2001)
T lymphocytes play a central role in the pathogenesis of a large number of human conditions including autoimmunity and graft rejection. Although T cells are key players in mounting immune responses, the assessment of T cell repertoires has yet to find an important role in clinical decision making. In this review, we discuss the “immunoscope” technique and its potential diagnostic role in a variety of clinical scenarios. This is an RT-PCR based approach that subdivides a bulk T cell population (i. e. from blood, lymph, spleen, or tissue) into approximately 2800 groups based upon rearranged variable beta (V beta) / joining beta (J beta) gene segments and the resulting length of the T cell receptor (TCR) third complementarity determining region (CDR-3). This extensive subdivision, or focusing, allows clonal expansions to be directly observed. Such a fine-tuned analysis has revealed previously unappreciated aspects of the T cell repertoire. For instance, an antigen-specific immune response can be divided into both public and non-public components. The non-public repertoire contains the majority of the expanding T cells which are unique to the individual (private), or shared by only some (semi-private), while ”public” T cells can be found responding to the antigenic determinant in every individual. Although they are often a minority of the response, the public T cell repertoire seems to play a more important role in defining, as well as driving, the overall immune phenotype in the animal. Immunoscope analysis has identified public and non-public responses in human pathologies, such as multiple sclerosis. The ability to characterize the driver T cells dictating the state of immunity / autoimmunity in individual patients will be an important step towards understanding autoimmunity and designing effective treatment for a variety of conditions including rheumatoid arthritis and multiple sclerosis. We review the current literature involving public and non-public repertoires and discuss the prospect that immunoscope analysis may play a central role in the study and perhaps the management of human autoimmune diseases, and cancer.
Keywords: Autoimmune Diseases